Association between intensive glycemic control and mortality in elderly diabetic patients in the primary care: A retrospective cohort study. Issue 5 (October 2020) - Ying, Derek GC; Ko, SH; Li, YC; Chen, Catherine XR
Highlights: Both high and low HbA1c were associated with higher mortality in elderly diabetics. A 3-fold increase in odd ratio for mortality was noted when the HbA1c was <6.0%. Risk factors for mortality included smoking, low BMI, high LDL, and sulphonylureas. Aggressive glycaemic control should be approached cautiously in the elderly. Abstract: Objective: To examine the association between the most recent HbA1c values and the mortality of elderly Type 2 Diabetic (T2DM) patients managed in the public primary care setting and to explore the associating risk factors. Design: Retrospective cohort study. Subjects: All T2DM patients aged 65 or above, who attended a public primary care clinic for regular follow up from 01/01/2012 to 31/12/2012 were included. Their follow up status till 31/12/2017 was reviewed. Those who were deceased on or before 31/12/2017 were matched randomly with controls that were alive in the same cohort for comparison. Main Outcome Measures: Patients' demographics, smoking status, duration of T2DM, biochemical parameters including the most recent HbA1c, lipid profile, renal function test, drug profile, co-morbidities and all-cause mortality were retrieved from Hospital Authority's CDARS and CMS systems. Results: Both high (>8.0%) and low (<6.5%) HbA1c values were associated with increased odd ratio of all-cause mortality among T2DM elderly patients treated in the primary care. There was a 3-fold increase in odd ratio when the HbA1c reading was very low (<6.0%). Associated risk factors for all-cause mortality in elderly T2DM patients included smoker status, lower BMIs, and higher LDL levels and use of sulphonylureas. Conclusions: Glycemic target for elderly T2DM patients should be approached cautiously. Over-aggressive treatment may lead to increased mortality among elderly T2DM patients.